The role of gut microbiota in myocardial ischemia-reperfusion injury - Chen, Xin; Ye, Lu; Zou, Xin; Zhou, Yuan; Peng, Chan; Huang, Rui (Frontiers in Cardiovascular Medicine, 2025)
Myocardial ischemia-reperfusion injury denotes the pathological damage resulting from the restoration of blood flow and oxygen supply following acute coronary artery occlusion. Myocardial ischemia-reperfusion injury is commonly seen in acute coronary syndromes and is an important factor in the development of ischemic cardiomyopathy, which severely affects the prognosis of coronary heart disease. The gut microbiota, a complex ecosystem with multifaceted functions, plays a crucial role in host health. Dysregulation of the gut microbiota exerts substantial effects on the onset and progression of cardiovascular diseases, including myocardial ischemia-reperfusion injury. This review elucidates the mechanisms underlying myocardial ischemia-reperfusion injury and the involvement of the gut microbiota in this process, encompassing aspects such as intestinal barrier integrity, microbial dysbiosis, inflammatory responses, oxidative stress, mitochondrial dysfunction, and metabolic alterations. Additionally, we investigate various interventions that modulate myocardial ischemia-reperfusion injury by influencing the gut microbiota. Maintaining a healthy intestinal barrier and a stable microbial ecology is paramount in preventing myocardial ischemia-reperfusion injury. High-fiber diets, probiotic consumption, short-chain fatty acids supplementation, and Traditional Chinese Medicine, can safeguard the heart against myocardial ischemia-reperfusion injury by regulating gut microbiota through diverse mechanisms. As the role of gut microbiota in myocardial ischemia-reperfusion injury continues to be investigated, it provides important therapeutic targets and drug development opportunities for the prevention and treatment of myocardial ischemia-reperfusion injury. However, further in-depth and comprehensive studies are required to fully realize these potentials.